Recurrent Coronary Vasospasm in a 50-Year-Old Woman with Granulomatous Polyangiitis: A Case Report - Hou L; Zhao J; He T; Luo Y; Su K; Li Y; Zhu R (Dove Medical Press, 2024)
Ling Hou,1,* Jinbo Zhao,2,* Ting He,1,* Yinhua Luo,3 Ke Su,2 Yuanhong Li,2 Ruiyang Zhu3 1Central Hospital of Tujia and Miao Autonomous Prefecture, Hubei University of Medicine, Shiyan, People's Republic of China; 2Cardiovascular Disease Center, Central Hospital of Tujia and Miao Autonomous Prefecture, Hubei University of Medicine, Enshi, Hubei Province, People's Republic of China; 3Center for Gene Diagnosis and Department of Clinical Laboratory Medicine, Zhongnan Hospital of Wuhan University, Wuhan, Hubei Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuanhong Li, Cardiovascular Disease Center, Central Hospital of Tujia and Miao Autonomous Prefecture, Hubei University of Medicine, Enshi, 445400, People's Republic of China, Email lyh0101@vip.163.com Ruiyang Zhu, Center for Gene Diagnosis and Department of Clinical Laboratory Medicine, Zhongnan Hospital of Wuhan University, Wuhan, 430071, People's Republic of China, Email zhuruiyang@whu.edu.cnAbstract: Granulomatosis with polyangiitis (GPA) is a necrotizing granulomatous vasculitis classified as an autoimmune small-vessel vasculitis. Clinically, approximately 80% of affected organs in GPA involve the upper/lower respiratory tract and kidneys, with cardiovascular system involvement being rare. Here, we report a case of a 50-year-old female patient who presented with sudden-onset chest pain lasting for 1 hour. The patient had normal body temperature, and markers of infection such as C-reactive protein and erythrocyte sedimentation rate were within normal limits. Electrocardiography revealed ST-segment elevation in inferior, precordial, and posterior leads. Emergency coronary angiography showed no significant obstructive disease, prompting consideration of vasospastic angina given the patient's recurrent chest pain symptoms and findings on laboratory and imaging studies. The patient underwent treatment including coronary vasospasm antagonists and immunomodulation, resulting in clinical improvement and subsequent discharge. During a 7-month follow-up period, the patient did not experience any further adverse cardiovascular events.Keywords: granulomatosis with polyangiitis, vasospastic angina, case report